MODIFICATION POLISAKARIDA GALAKTOSA SULPHATE EXTRACTION EXPORT FROM GRACILARIA SP (ALGA MERAH) WITH ALKALI BOROHIDRIDA - Atun, Sri (Jurnal Penelitian Saintek, 2015)
The objective of the study is to modify the sulphate galactanspolysaccharide (gelatine) provided from extraction of Gracilaria sp with borohydride alkali and its result characterization. The sample of this study was the sulphate galactans polysaccharide provided from extraction of Graci/aria sp. The modified reaction using the Rees method used NaBH4 and NaOH in various compositions. The physical and chemical characteristics of the modification reaction results were compared to the characteristics of the seaweed gelatine provided from the extraction before the treatment and agarosa p.a. The result of this study indicates that the sulphate galactans polysaccharide can be modified by borohidrida alkali reagent in base condition at the composition variations of the seaweed gelatine: NaBH4 : NaOH = 1: 0,5 : ] ; 1 : 1 : 2 and 1: 2 : 4 .The characterization showed that the compound of the modification reaction result compared to the sulphate galactans polysaccharide before the treatment indicated the change of their physical and chemical characteristics. The characteristics of the compound resulted from modification reaction of sulphate galactans polysaccharide at the composition variations of the seaweed gelatine: NaBH4 : NaOH = 1 : 1 : 2 and 1 : 2 : 4 were almost similar to the characteristics of agarosa p. a.